Impact of Inaccurate Documentation of Sampling and Infusion Time in Model-Informed Precision Dosing - Alihodzic, Dzenefa; Broeker, Astrid; Baehr, Michael; Kluge, Stefan; Langebrake, Claudia; Wicha, Sebastian Georg (Frontiers in Pharmacology, 2020)
Routine clinical TDM data is often used to develop population pharmacokinetic (PK) models,which are applied in turn for model-informed precision dosing. The impact of uncertainty in documented sampling and infusion times in population PK modeling and model-informed precision dosing have not yet been systematically evaluated. The aim of this study was to investigate uncertain documentation of (i)sampling times and (ii)infusion rate exemplified with two anti-infectives. A stochastic simulation and estimation study was performed in NONMEM® using previously published population PK models of meropenem and caspofungin. Uncertainties,i.e. deviation between accurate and planned sampling and infusion times (standard deviation ±5 min to ±30 min) were added randomly in R before carrying out the simulation step. The estimation step was then performed with the accurate or planned times (replacing real time points by scheduled study values). Relative bias (rBias) and root mean squared error (rRMSE) were calculated to determine accuracy and precision of the primary and secondary PK-parameters on the population and individual level. The accurate and the misspecified (using planned sampling times) model were used for Bayesian forecasting of meropenem to assess the impact on PK/PD-target calculations relevant to dosing decisions. On the population level,the estimates of the proportional residual error (prop.-err.) and the interindividual variability on the central volume of distribution (V1) were most affected by erroneous records in the sampling and infusion time (e.g. rBias of prop.-err.: 75.5% vs. 183% (meropenem) and 10.1% vs. 109% (caspofungin) for ±5 vs. ±30 min, respectively). On the individual level, the rBias of the planned scenario for the typical values V1,Q and V2 increased with increasing uncertainty in time,while CL, AUC and elimination half-life were least affected. Meropenem as a short half-life drug (~1 hour) was more affected than caspofungin (~9-11 hours). The misspecified model provided biased PK/PD-target information (e.g. falsely overestimated time above MIC (T>MIC) when true T>MIC was <0.4 and thus patients at risk of undertreatment),while the accurate model gave precise estimates of the indices across all simulated patients. Even 5-minute-uncertainties caused bias and significant imprecision of primary population and individual PK-parameters. Thus,our results underline the importance of accurate documentation of time.